Meta-analysis of α-blockade versus no blockade before adrenalectomy for phaeochromocytoma - Schimmack, Simon; Kaiser, Jörg; Probst, Pascal; Kalkum, Eva; Diener, Markus K.; Strobel, Oliver (The British journal of surgery, 2020)
Background Preoperative α-blockade in phaeochromocytoma surgery is recommended by all guidelines to prevent intraoperative cardiocirculatory events. The aim of this meta-analysis was to assess the benefit of such preoperative treatment compared with no treatment before adrenalectomy for phaeochromocytoma. Methods A systematic literature search was undertaken in MEDLINE, Web of Science and CENTRAL without language restrictions. Randomized and non-randomized comparative studies investigating preoperative α-blockade in phaeochromocytoma surgery were included. Data on perioperative safety, effectiveness and outcomes were extracted. Pooled results were calculated as an odds ratio or mean difference with 95 per cent confidence interval. Results A total of four retrospective comparative studies were included investigating 603 patients undergoing phaeochromocytoma surgery. Mortality, cardiovascular complications, mean maximal intraoperative systolic and diastolic BP, and mean maximal intraoperative heart rate did not differ between patients with or without α-blockade. The certainty of the evidence was very low owing to the inferior quality of studies. Conclusion This meta-analysis has shown a lack of evidence for preoperative α-blockade in surgery for phaeochromocytoma. RCTs are needed to evaluate whether preoperative α-blockade can be abandoned.
Gesehen am 30.01.2020
Im Titel ist "alpha" als griechischer Buchstabe dargestellt